Why worry about the politics of childhood undernutrition? - Nisbett, Nicholas; Gillespie, Stuart; Haddad, Lawrence; Harris, Jody (Elsevier, 2014)
Undernutrition affects over 2 billion people; but most of the global policy focus has been on technical solutions rather than an understanding of nutrition politics. This paper reviews existing literature on nutrition politics and policy. We identify a number of recurring themes surrounding knowledge; politics, and capacities. While the literature on nutrition politics and policy is growing; we demonstrate how there are a number of gaps in our understanding that might be addressed from wider development scholarship on politics and related issues such as power and the state, participation, and accountability.